2017
DOI: 10.25215/0501.084
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Depression among freshmen and Last Year College Students

Abstract: Background: Going off to college is a unique point in time for young adults. It forces independence from a developed comfort zone that folks may have had through the end of high school, and at the same time drives home the point that there is no one around to clean up one’s mistakes anymore. The purpose of this study was to measure the depression among college freshmen and last year college students. Methods: Two groups were selected one is of freshmen and the other is of last year, both groups have 60 student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Past studies have shown that mental health problems are common among students, which involve low to severe levels (Bastaminia et al, 2016;Irfan and Akhtar, 2020;Islam et al, 2018;Pandey, 2017;Puthucheary et al, 2011;Samsudin and Hong, 2016;Yahya et al, 2017). As a result of the COVID-19 pandemic, mental health issues have also been increasing among students (Chang et al, 2020;Gao and Zheng, 2011;Lee, 2020;Liu et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Past studies have shown that mental health problems are common among students, which involve low to severe levels (Bastaminia et al, 2016;Irfan and Akhtar, 2020;Islam et al, 2018;Pandey, 2017;Puthucheary et al, 2011;Samsudin and Hong, 2016;Yahya et al, 2017). As a result of the COVID-19 pandemic, mental health issues have also been increasing among students (Chang et al, 2020;Gao and Zheng, 2011;Lee, 2020;Liu et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%